PURWARUPA SISTEM SORTING BARANG BERDASARKAN WARNA MENGGUNAKAN MIKROKONTROLER ATMEGA16 DENGAN SENSOR PHOTODIODA - , BRIAN EKA BUANA; , Drs. Panggih Basuki, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the industrial world, the company is in need of saving time, expenses, and getting a good accuracy in production. Production of an item will be referring to the economic principle that where we have capital but produce at least as much. This item separator system will be very useful to save time in production because it does not require an operator to sort items. This thesis aims to develop a prototype that serves to separate the two different objects to save time and improve accuracy in the separation of goods. In the separation of goods, used automatically on a conveyor belt using atmega 16 microcontroller. A microcontroller is a single chip that can be programmed to perform a wide variety of execution based on the desire of programmers. The tool is also able to communicate well with each other with a microcontroller or other devices such as a PC either in series or parallel. To program the microcontroller, we need a special software. Programs can be written using language BASCOM AVR. This process is used in the output of the microcontroller ATmega16 ATMEL series and using the software used to download the program to the microcontroller atmega16 named USB ASP. Based on the results of tests performed, it can be concluded that this item separator system can work well in accordance with the working principles designed. Keywords: System separators goods, Photodioda, Servo Motor, DC Motor, LCD 16x2